(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3JHOC HJQLeI dCHi HcQ GdUOjb , hGdehLhO efgG , bhdg (B: (3bMGaI YKeGf Hf YGeQ Hf YeQh Hf cYH Geg Sdei , hJcfi Ce GdNjQ HfJ UNQ Hf YGeQ ehdOg Hefi HYO YGe Gdajd HKdGK Sfjf s
(3BNQgG (B:s
(3jfJgi ef MhGOK SfI NeS hKeGf eFg , bhdg (B: (3aQLY GdSdWGf hef ai NOeJg Edi GdbdYI GdefUhQI eDjOkG efUhQkG Ke Mce HYO Pdc hCQSdhG Edi KZQ GdCScfOQjI hGSJbQ GdCejQ jTHc OhGhOGQ Ydi YGOJg HYO eOI , hajgG MVQhG gPG eG GfJgi EdjfG ef GdLRAs
(3fSNI KGfjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B57 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B45 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs